ANALYSIS OF THE SPHERES OF APPLICATION OF UNMANNED AIRCRAFT APPARATUS FOR RESOLVING LABOR SAFETY ISSUES - Krainiuk, О.; Buts, Yu.; Barbashyn, V.; Didenko, N. (Municipal economy of cities. Series: «Economy science», 2023)
An analysis of the use of unmanned aerial vehicles has been provided, and they can be effectively used to monitor and control the implementation of safe working conditions. Recently, there has been a growing trend of using UAVs with various sensors and other digital technologies. Dangers that can be caused by the drones themselves have been identified. Efficient deployment of drones for security review will require further research, better understanding of how this technology can be deployed for the operation of a security management system. In this report, an assessment of the number of drones for security checks is presented. The method of work is to develop recommendations on how to check the safety of drones for re-checking the safety and assigning the role of drones for the establishment of administrative tasks of the system for managing the security work on re-checking the safety, revealing that correcting the shortcomings, and protecting the accidents. There is a risk of unintended physical interaction between UAVs and other objects, potentially leading to accidents or injuries. These injuries can occur from several sources, such as:technical errors: hardware or software errors;human errors: errors in navigation; environmental factors (weather conditions); cyber-attacks: hacking of a UAV with a nefarious purpose. Consequently, UAVs may create hazardous conditions such as the inability to stop, deviate from the planned flight path, fly at uncontrolled speeds or make sudden movements, which may cause the UAV to collide or fall and cause unintended physical contact. UAVs can be a source of distraction or preoccupation. The sight or sound of UAVs can distract workers. It is known that drivers were distracted by drones, which led to accidents. The application of advanced technologies in the field of occupational health and safety can provide a practical means for the occupational health and safety service to monitor and control the operation of the OSH. The study examined the ways of using drones to increase the level of safety, and also identified the risks of the use of UAVs: the risk of physical contact, loss of attention, psychological impact, but the benefits of using drones can be much more important, so the safety of using drones should be studied in detail, adding changes in relevant regulatory and legal documents on labor protection and gradually introduce leading technologies to improve working conditions.